2002
DOI: 10.1530/eje.0.1470777
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha gene polymorphisms Pvu II and Xba I influence association between leptin receptor gene polymorphism (Gln223Arg) and bone mineral density in young men

Abstract: Objective: The peak bone mass is recognized as an important determinant in the development of osteoporosis. We investigated associations between bone mineral density (BMD) and polymorphisms of the leptin receptor (LEPR) and estrogen receptor a (ERa) genes in young men. Design: BMD, anthropometric characteristics, and serum leptin concentrations were measured in young men and compared with regard to the LEPR and ERa genotype. Methods: From 219 healthy volunteers aged 20 -34 years, we genotyped the Lys109Arg, Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 41 publications
4
17
0
2
Order By: Relevance
“…In a study of the Ningxia Hui population in China, lepR SNP A668G exerted an association with susceptibility to knee osteoarthritis, meaning that the SNP may be regarded as one of the candidate genes to predict the risk of knee osteoarthritis [117], but whether lepR SNP A668G affects susceptibility to RA still needs more research. Yiannakouris et al [118] and Koh et al [119] found that LepR A668G related to plasma levels of leptin, as mentioned previously. This difference suggested that LepR gene SNPs may be susceptible to genetic background and environmental factors in various ethnic populations.…”
Section: Genetic Studies Concerning Leptin In Rasupporting
confidence: 65%
“…In a study of the Ningxia Hui population in China, lepR SNP A668G exerted an association with susceptibility to knee osteoarthritis, meaning that the SNP may be regarded as one of the candidate genes to predict the risk of knee osteoarthritis [117], but whether lepR SNP A668G affects susceptibility to RA still needs more research. Yiannakouris et al [118] and Koh et al [119] found that LepR A668G related to plasma levels of leptin, as mentioned previously. This difference suggested that LepR gene SNPs may be susceptible to genetic background and environmental factors in various ethnic populations.…”
Section: Genetic Studies Concerning Leptin In Rasupporting
confidence: 65%
“…In the literature, data on the relation between LEPR mutations and bone metabolism are scarce. Two studies in young male subjects suggest a positive effect of the Gln-allele on bone acquisition involving a possible interaction with other genotypes (20) or with lifestyle-related factors such as physical activity (24).…”
Section: Discussionmentioning
confidence: 99%
“…The human brain leptin receptor gene (LEPR) is encoded in 20 exons and spans over 70 kb of DNA (13). Previous studies revealed several sequence variants in the LEPR gene (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), but mostly without any obesity-causing association (15,16,18). Some studies described association with serum leptin levels (13,19,22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale evidence of the contribution of ESR1 genetic variation to osteoporosis risk in men is lacking; a few studies reported association with BMD in men (Long et al, 2004) but most found no association (Langdahl et al, 2000;Khosla et al, 2004;Koh et al, 2002;van Meurs et al, 2003). In this context, it is notable that Khosla et al (Khosla et al, 2004) found significant interactions between bioavailable estradiol levels and the XbaI and PvuII genotypes on rates of bone loss in men aged 22-90 years.…”
Section: Estrogen Receptors α (Esr1) and β (Esr2) Gene Polymorphismsmentioning
confidence: 99%